Best Answer

The question consists of an algebraic expression. There is no equation nor inequality which may be solved.

Q: 13x - (3x6)z

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

13x = 91To solve for x, divide both sides of the equation by 13.13x/13 = 91/13x = 91/13 = 7

6x2+13x-5 = (2x+5)(3x-1) when factored

3x2+13x-10 = (3x-2)(x+5) when factored

x2 + 13x + 36 = (x + 9)(x + 4)

(x + 1)(3x + 10)

Related questions

13x-11y-12 11 11 13x-1 -13x-13x=12

13x

13x-10x = 3

13x - 4x = 9

(13x)2 = 169x2

-x^2 -13x -40 = -(x^2 + 13x + 40) = -(x + 5)*(x + 8)-x^2 -13x -40 = -(x^2 + 13x + 40) = -(x + 5)*(x + 8)-x^2 -13x -40 = -(x^2 + 13x + 40) = -(x + 5)*(x + 8)-x^2 -13x -40 = -(x^2 + 13x + 40) = -(x + 5)*(x + 8)

13x-14 or 13x+(-14)

The GCF is 13x

Clarence 13X was born on February 22, 1928.

Clarence 13X was born on February 22, 1928.

5x^2 - 13x = x(5x - 13)

7+3w-13x